2017
DOI: 10.2215/cjn.12721216
|View full text |Cite
|
Sign up to set email alerts
|

“Maybe They Don't Even Know That I Exist”: Challenges Faced by Family Members and Friends of Patients with Advanced Kidney Disease

Abstract: Background and objectives Family members and friends of patients with advanced chronic illness are increasingly called on to assist with ever more complex medical care and treatment decisions arising late in the course of illness. Our goal was to learn about the experiences of family members and friends of patients with advanced kidney disease.Design, setting, participants, & measurements As part of a study intended to identify opportunities to enhance advance care planning, we conducted semistructured intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…The work described here was conducted as part of a single-center study on advance care planning (11,12). This study enrolled patients receiving care in the 1 Center of Innovation for Veteran-Centered and Value-Driven Care, 2 Nephrology Section, Hospital and Specialty Medicine Service, and Nephrology clinic or dialysis unit at the VA Puget Sound Health Care System in Seattle, Washington, who had an eGFR#20 ml/min per 1.73 m 2 on at least two occasions 3 months apart or were undergoing treatment with maintenance dialysis.…”
Section: Recruitmentmentioning
confidence: 99%
“…The work described here was conducted as part of a single-center study on advance care planning (11,12). This study enrolled patients receiving care in the 1 Center of Innovation for Veteran-Centered and Value-Driven Care, 2 Nephrology Section, Hospital and Specialty Medicine Service, and Nephrology clinic or dialysis unit at the VA Puget Sound Health Care System in Seattle, Washington, who had an eGFR#20 ml/min per 1.73 m 2 on at least two occasions 3 months apart or were undergoing treatment with maintenance dialysis.…”
Section: Recruitmentmentioning
confidence: 99%
“…In the context of this earlier work, our findings indicate that there has been limited progress over the last several decades in family members' understanding of the values and preferences of people undergoing dialysis and highlight some of the challenges involved in supporting the advance care planning process (17,(23)(24)(25). Qualitative studies among family members of people both with (24,26) and without kidney disease (27,28) speak to the complex dynamics of engaging family members in patients' care. Similar to other chronic conditions (27,29), it is not unusual for the family members of people with advanced kidney disease to become involved in their care relatively late in the course of illness in situations of crisis or increasing care needs, at which time their involvement is often expected and prompted by the health system (17,24).…”
Section: Discussionmentioning
confidence: 67%
“…8 Yet, care partners of persons receiving hemodialysis report they feel their role is often overlooked in the clinical care plan. 31 Notably, others have shown that less social support is also associated with worse mortality among dialysis-dependent adults. 6 , 7 To address this disconnect, employing models of kidney care that incentivize care coordination, such as those within the Kidney Care Choices model, 32 may be one potential solution.…”
Section: Discussionmentioning
confidence: 99%